1994
DOI: 10.3102/00028312031001138
|View full text |Cite
|
Sign up to set email alerts
|

Task Talk and Task Awareness Under Different Cooperative Learning Conditions

Abstract: This study examined the effects of two cooperative conditions on group discussions and metacognitive awareness. The reward condition used rewards to encourage group interdependence, whereas the strategic condition more directly emphasized the connection between strategy use and learning. Four 4th- and four 5th-grade classrooms participated. Cooperative discussions were observed over a 2-week period, and awareness was assessed through interviews that followed observations. The form of peer-group talk (e.g., fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…In line with past studies on task communication and collaboration processes in groups and teams (Chiu, 2004;Jonassen & Kwon, 2001;Meloth & Deering, 1994;Orvis, Wisher, Bonk, & Olson, 2002), we also examine how preceding verbal behaviors may influence the ignition and resolution of disagreement episodes within the team interaction flow (see Figure 1), as past studies show that temporal dynamics during team conversations can affect team functioning and effectiveness. For example, a qualitative study of board meetings highlights conversational dynamics at the core of creative team processes and describes the concept of interaction flow as "an optimal, intensified, and synergetic mode of the conversational interaction within a small group" (Van Oortmerssen, Van Woerkum, & Aarts, 2015, p. 522).…”
Section: Behavioral-level Influences: Problem-solving and Off-task mentioning
confidence: 77%
“…In line with past studies on task communication and collaboration processes in groups and teams (Chiu, 2004;Jonassen & Kwon, 2001;Meloth & Deering, 1994;Orvis, Wisher, Bonk, & Olson, 2002), we also examine how preceding verbal behaviors may influence the ignition and resolution of disagreement episodes within the team interaction flow (see Figure 1), as past studies show that temporal dynamics during team conversations can affect team functioning and effectiveness. For example, a qualitative study of board meetings highlights conversational dynamics at the core of creative team processes and describes the concept of interaction flow as "an optimal, intensified, and synergetic mode of the conversational interaction within a small group" (Van Oortmerssen, Van Woerkum, & Aarts, 2015, p. 522).…”
Section: Behavioral-level Influences: Problem-solving and Off-task mentioning
confidence: 77%
“…Both the intersubjective attitude of collaborators and the extent to which the attention and effort of partners were coordinated were the key to understanding the accomplishment or the failure of communication. Cohen (1996), Meloth and Deering (1994), and Webb and Farivar (1994) suggested that mathematical interaction in small group activities must be structured. This is needed to maximize the opportunities for each student to be engaged in questioning, elaboration, explanation, and other verbal communication in which students can express their ideas and through which the group members can give and receive feedback.…”
Section: Cooperative Learningmentioning
confidence: 99%
“…The limitation of the collaborative approach is that students may not be motivated to contribute more to the group’s work, knowing that they will all receive the same grade (Roberts & McInnerney, ). Cooperative group work can tackle this shortcoming of collaborative group work, since in cooperative group work, members are assigned tasks individually, and therefore, students pay more attention to the task itself and the substantial contents in the task (for example, Meloth & Deering, ). “Characteristics of cooperative learning include division of labor, task specialization, and individual responsibility for part of the final product” (Paulus, , p. 112), as well as interdependence (Rose, ).…”
Section: Literature Reviewmentioning
confidence: 99%